Digital Multilingualism, Creative Expression, and Youth Identity: Educational Perspectives on English Loanwords in Online Communication - Isabelle Martin (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2015)
This study investigates the role of English loanwords in shaping youth identity, with a focus on their linguistic, artistic, and educational implications in digital communication. Using a quantitative survey design, data were collected from 410 high school and university students through structured questionnaires assessing language attitudes, identity construction, and patterns of digital language use. Participants responded to Likert-scale items addressing perceptions of modernity, cultural affiliation, and language preservation. The data were analyzed using factor analysis and regression techniques to identify key attitudinal dimensions and their influence on language practices. The findings indicate that English loanwords are widely embraced as resources for creative expression and identity performance in digital contexts. While participants expressed strong appreciation for global linguistic trends, they also emphasized the importance of preserving local languages as part of their cultural identity. This study highlights the need for language education to move beyond rigid monolingual frameworks by acknowledging digital multilingualism as a legitimate and valuable component of contemporary communication. Educators and policymakers are encouraged to integrate students’ digital language practices into pedagogical strategies to enhance engagement, creativity, and linguistic awareness.